(untitled) (ENTHYMEMA, 2023)
When Orlando Furioso di Ludovico Ariosto raccontato da Italo Calvino was published in 1970, it was presented as a «reading guide». This contribution aims to leave behind this definition and to prove not only that Calvino’s rewriting of Orlando Furioso is an independent literary work – although born in function of Ariosto’s epic poem –, but also that this consideration is the key issue to understand its success as a divulgation tool. Calvino and Einaudi found in the rewriting of the epic poem by a contemporary author a «new kind of mediation» between the public and the classics: an original narrative in dialogue with Ariosto’s work, that refused to adopt a pedagogical attitude towards readers. The analysis of the word will be conducted through the reconstruction of its genesis, the observations on style and rewriting techniques, the focus on its bond with contemporary Calvino’s production, especially the one about Ariosto.